Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation (GI) dalam Menulis Teks Puisi Siswa Kelas VIII SMP - Dela, Juni Alfi; Tamsin, Andria Catri; Amir, Amril; Nofrahadi, Nofrahadi (Universitas Muhammadiyah Magelang, 2026)
This study has the following objectives. First, to describe the planning for implementing the GI Cooperative Learning Model in writing poetry texts for eighth-grade students at UPT SMP N 1 Pancung Soal. Second, to describe the implementation of the GI Cooperative Learning Model in writing poetry texts for eighth-grade students at UPT SMP N 1 Pancung Soal. Third, to describe the evaluation of the implementation of the GI Cooperative Learning Model in writing poetry texts for eighth-grade students at UPT SMP N 1 Pancung Soal. This research is a qualitative study using descriptive methods. The results indicate that: First, the planning for implementing the GI Cooperative Learning Model in writing poetry texts for eighth-grade students at UPT SMP N 1 Pancung Soal is optimal. The teacher has determined the learning topic and subtopics, compiled a module containing the syntax of the GI Cooperative Learning Model, created an assessment rubric, prepared learning media, and teaching materials. Second, the implementation of the GI Type Cooperative learning model in writing poetry texts for class VIII students of UPT SMP N 1 Pancung Soal has been carried out by the implementing teacher. Third, the evaluation of learning skills in writing poetry texts using process and outcome evaluation with assessment and observation rubrics, found that the implementation process was in accordance with the planning. Thus, it can be concluded that students' poetry writing skills have been at a good category level in accordance with the rules for writing good and correct poetry texts.